2017
DOI: 10.1111/obr.12557
|View full text |Cite
|
Sign up to set email alerts
|

Electronic‐based lifestyle interventions in overweight or obese perinatal women: a systematic review and meta‐analysis

Abstract: Electronic-based (e-based) lifestyle interventions provide potential and cost-effective delivery of remote interventions for overweight and obese perinatal women. To date, no meta-analysis has reported the efficacy of maternal and neonatal outcomes. Seven electronic databases were searched from inception up to July 13, 2016, including the Cumulative Index to Nursing and Allied Health Literature, Cochrane Library, EMBASE, ProQuest Dissertations and Theses, PsycINFO, PubMed and Scopus. Among the 1,145 studies re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
99
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(100 citation statements)
references
References 84 publications
(235 reference statements)
1
99
0
Order By: Relevance
“…Seven of the nine systematic reviews had performed meta‐analyses, while two reported only a narrative synthesis . No systematic review included exactly the same RCTs.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Seven of the nine systematic reviews had performed meta‐analyses, while two reported only a narrative synthesis . No systematic review included exactly the same RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…The definition of the postnatal period also varied between systematic reviews. Three defined this as up to 12 months after childbirth, one up to 18 months, and one up to 24 months . The remaining four systematic reviews stated that they included studies with postnatal women but did not define the postnatal period …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations